Occurrence of Triggerfishes in Wadge Bank Trawl Catches - K.K., Kunjipalu (Fishery Technology, 2025)
Substantial quantities of triggerfishes (Family: Balistidae) were caught in the Wadge Bank off the southwest coast of India using a 50 m high opening trawl during cruise no. 110 of FORV Sagar Sampada in July 1993. Average CPUE of triggerfishes was 1482 kg h-1 constituting 69.5% of the landings in the grounds where they were caught.